Mediating Effect of Emotional Symptoms on the Association Between Alexithymia and Substance Dependence in Patients with Substance Use Disorder: The Protective Role of Family Support and Self-Efficacy - Li DJ; Wu HC (Psychology Research and Behavior Management)
Dian-Jeng Li,1,2 Hung-Chi Wu1,3,4 1Department of Addiction Science, Kaohsiung Municipal Kai-Syuan Psychiatric Hospital, Kaohsiung, Taiwan; 2Department of Nursing, Meiho University, Pingtung, Taiwan; 3Department of Nursing, Fooyin University, Kaohsiung, Taiwan; 4College of Medicine, Kaohsiung Medical University, Kaohsiung, TaiwanCorrespondence: Dian-Jeng Li, Department of Addiction Science, Kaohsiung Municipal Kai-Syuan Psychiatric Hospital, 130, Kai-Syuan 2nd Road, Ling-Ya District, Kaohsiung, 802, Taiwan, Tel +886-7-751-3171 ext. 2317, Fax +886-7-16-1843, Email edcrfvm45@hotmail.comBackground: The etiology of the association between alexithymia and substance use is complex, and there is an urgent need to explore the related factors. The aims of this study were to develop a conceptual model to verify the mediating effect of emotional symptoms and moderating effect of family support and self-efficacy on the association between alexithymia and substance dependence.Methods: A total of 117 participants (103 males and 14 females; age at 35.29 ± 8.72 years) with substance use disorder were analyzed. Outcome measures included demographic characteristics, severity of dependence, symptoms of alexithymia, emotional symptoms (depression, anxiety, and somatic symptoms), level of family support, and self-efficacy. The PROCESS macro in SPSS was used to estimate path coefficients and adequacy of the moderated mediation model, which was adjusted for demographic characteristics.Results: Most of the participants had amphetamine use disorder (n = 42, 35.9%). After controlling for the effects of demographic characteristics, the moderated mediation model showed that the association between alexithymia and substance dependence was mediated by emotional symptoms and moderated by family support and self-efficacy. A higher level of family support reduced the effect of alexithymia on emotional symptoms, and a higher level of self-efficacy reduced the effect of emotional symptoms on substance dependence.Conclusion: Family support and self-efficacy have a protective effect on the association between alexithymia and substance dependence in patients with substance use disorder. Early interventions to enhance these protective factors may be beneficial.Keywords: alexithymia, emotional symptom, family support, self-efficacy, substance use